If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(5x-1)=42
We move all terms to the left:
3(5x-1)-(42)=0
We multiply parentheses
15x-3-42=0
We add all the numbers together, and all the variables
15x-45=0
We move all terms containing x to the left, all other terms to the right
15x=45
x=45/15
x=3
| -8y-6=-2y+6 | | 6^x-5=25 | | 4400-400x=0 | | 4x-1+3x=-15 | | 3*x^2-6*x-9=0 | | 4/k+9=-2/k-5 | | 6x+13=2x+33 | | 4400-400x=3000 | | 26+7x=166 | | 26+7x=446 | | 2^r=1/16 | | 2r=1/16 | | 5(6d+8)=10(2d+7) | | 3m(58+43)=4(62+57)=55 | | 3c+3=5c+9 | | 3+3.5g=11-0.5g | | K(x)=3x | | 85+20x=785 | | 6x–14x=–8+2+(–42) | | -9w-12+10w=-2+9 | | 85+20x=765 | | 2(6x–3)=3(5x–7) | | F(x)=3x^2+30x-65 | | -4n+5=2-n | | 2x+3(x-2)=4(1-5x)-8 | | (x^2)+2x-10=0 | | 4-2k=-8+k | | 3-2x+20=4x-20 | | (2x+20)3=(4x20) | | 5(3x-1)-4=7(4-2x)+5 | | 2(x-3)+7=5-(2-x) | | .08x=1200 |